2017
DOI: 10.1002/2017ja024225
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Double Mesospheric Bore Over Europe

Abstract: Observations of a pair of mesospheric bore disturbances that propagated through the nighttime mesosphere over Europe are presented. The observations were made at the Padua Observatory, Asiago (45.9°N, 11.5°E), by the Boston University all‐sky imager on 11 March 2013. The bores appeared over the northwest horizon, approximately 30 min apart, and propagated toward the southeast. Using additional satellite and radar data, we present evidence indicating the bores originated in the mesosphere from a single, larger‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…Sharp propagating fronts of brightness jump or drop that are followed by a train of waves or turbulence have been occasionally observed in mesospheric airglow by ground-based imagers. Since Taylor et al (1995) first reported this type of event over Hawaii, similar wave events have been reported at various locations (e.g., Fechine et al, 2005;Giongo et al, 2018;Li et al, 2013Li et al, , 2019Narayanan et al, 2009;Nielsen et al, 2006;She et al, 2004;Smith et al, 2003Smith et al, , 2005Smith et al, , 2017. Dewan and Picard (1998) explained the Taylor et al (1995) event as a propagating discontinuity in a stable layer or duct, and they named it a mesospheric bore.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…Sharp propagating fronts of brightness jump or drop that are followed by a train of waves or turbulence have been occasionally observed in mesospheric airglow by ground-based imagers. Since Taylor et al (1995) first reported this type of event over Hawaii, similar wave events have been reported at various locations (e.g., Fechine et al, 2005;Giongo et al, 2018;Li et al, 2013Li et al, , 2019Narayanan et al, 2009;Nielsen et al, 2006;She et al, 2004;Smith et al, 2003Smith et al, , 2005Smith et al, , 2017. Dewan and Picard (1998) explained the Taylor et al (1995) event as a propagating discontinuity in a stable layer or duct, and they named it a mesospheric bore.…”
Section: Introductionmentioning
confidence: 67%
“…Some previous studies have shown the association between mesospheric bores and tropospheric cold front systems (Smith et al, , ; Yue et al, ). They reported a concurrent tropospheric cold front system with a similar alignment of the mesospheric bore and suggested that the gravity waves generated from the cold front system could have excited the mesospheric bore.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…where N is the Brunt-Väisälä frequency, k = 2π/λ is the horizontal wavenumber, c is the horizontal phase speed of the bore, u is the wind speed in the direction of bore propagation measured by meteor radar, and u zz is the second derivative of u with height z. Equation (13) is only valid under the WKB approximation, which means the vertical scale of wind and temperature profiles are larger than the vertical wavelength of the wave (Nappo, 2002;Smith et al, 2017). Figure 12 presents vertical wave number m 2 profiles derived from the meteor radar wind profiles shown in Figure 5b and the temperature profiles shown in Figure 6 at P1, P2, and P3.…”
Section: Propagation Environment Of the Borementioning
confidence: 99%
“…The bore divides nightglow into bright and dark regions. Since a mesospheric bore was first reported by Taylor et al (), many researchers have devoted much effort to investigating this interesting phenomenon using ground‐based all‐sky airglow imagers (Li et al, ; Medeiros et al, ; Narayanan et al, ; Nielsen et al, ; She et al, ; Shiokawa et al, ; Smith et al, , , , ; Yue et al, ), satellite observation (Miller et al, ), and models (Dewan & Picard, , ; Laughman et al, ; Seyler, ).…”
Section: Introductionmentioning
confidence: 99%